Procalcitonin versus CRP as an early indicator of fetal infection in preterm premature rupture of membranes - Canpolat, Fuat Emre; Yiğit, Şule; Korkmaz, Ayşe; Yurdakök, Murat; Tekinalp, Gülsevin (The Turkish Journal of Pediatrics, 2011)
The aim of this study was to examine the diagnostic sensitivity and specificity of C-reactive protein (CRP) and procalcitonin (PCT) in neonates who were born after preterm premature rupture of membranes (PPROM) and compare these with interleukin-6 (IL-6). The study involved 74 preterm neonates who were born after PPROM. IL-6, CRP, complete blood count and leukocyte ratios, and PCT levels were measured in the 1st day of life, and CRP, PCT, and blood counts were repeated on the 3rd day of life. Seventy-four infants with PPROM were divided into two groups according to the development of sepsis and infection (Group 1: sepsis, n = 32; Group 2: no sepsis, n = 42). There were no significant differences between these groups with respect to gestational age, birthweight and duration of membrane rupture. There were significant differences between the two groups in the 1st day CRP (Group 1: 0.85 -/+ 1.36 mg/dl, Group 2: 0.23 +/- 0.25 mg/dl; p = 0.016), 1st day PCT (Group 1: 7.2 +/- 7.6 ng/ml, Group 2, 1.6 +/- 4.0 ng/ml; p < 0.001), and 3rd day PCT (Group 1: 9.01 +/-11.5 ng/ml, Group 2: 1.34 +/- 1.35 ng/ml; p = 0.001) and IL-6 (Group 1: 80.7 +/- 67.2 pg/ml, Group 2: 3.4 +/- 3.5 ng/ml; p < 0.001) levels. CRP levels were not significantly different between Group 1 (1.2 +/- 1.7 mg/dl) and Group 2 (0.58 +/- 1.1 mg/dl) on the 3rd day of life (p=0.059). CRP levels on the 1st day of life had a cut-off value of 0.72 mg/dl with a sensitivity and specificity of 56% and 58%, respectively. CRP levels on the 3rd day had a cut-off level of 0.78 mg/dl with 60% sensitivity and 63% specificity. PCT levels had a cut-off level of 1.74 ng/ml with 76% sensitivity and 85% specificity on the 1st day of life, and of 1.8 with 89% sensitivity and 86% specificity on the 3rd day of life. Statistical analysis revealed that the cut-off value of 7.6 pg/ml for IL-6 had a 93% sensitivity and 96.7% specificity. Interleukin (IL)-6 is the most reliable marker for the detection of early-onset sepsis in preterm neonates with PPROM. Early PCT levels seemed to be more sensitive than early CRP in this population.